PLOTTER 2D MENGGUNAKAN SERVO R88M-KE75030H-S2 PADA PROGRAMABLE LOGIC CONTROLLER OMRON CJ2M - Andy, An Pherta; Harianto, Harianto; Susanto, Pauladie (Journal of Control and Network Systems (JCONES), 2016)
Industry competition is increased encourage the emergence of Programmable Logic Controller (PLC) as a new controller for substitute a relay module. Programmable Logic Controller (PLC) to meet almost all of the expectations of the industry like as the speed of production, small maintenance costs, lower production costs and can improve product quality. That factors make a Programmable Logic Controller (PLC) be used in almost all industrial.Most plotter 2D that was created using stepper motors or DC motors. Both of these motors do not have the ability to move precision. Therefore, in this research will be made plotter 2D using AC servo motors as a replacement for stepper motors or DC motors used in other 2D plotter. Plotter 2D will be made with controlled or processed Omron PLC CJ2M CPU32 and makes the HMI (Human Machine Interface) as the media to enter the pattern image.From this research, do 20 trials in each pattern, with 5 the existing pattern and gained success rate of 99.87%.